Laboratory verification of the Active Particle-induced X-ray Spectrometer (APXS) on the Chang'e-3 mission. (November 2015) - Zhang, Guang-Liang; Li, Chun-Lai; Fu, Xiao-Hui; Zhang, Li-Yan; Ban, Cao; Li, Han; Zou, Yong-Liao; Peng, Wen-Xi; Cui, Xing-Zhu; Zhang, Cheng-Mo; Wang, Huan-Yu
Abstract: In the Chang'e-3 mission, the Active Particle-induced X-ray Spectrometer (APXS) on the Yutu rover is used to analyze the chemical composition of lunar soil and rock samples. APXS data are only valid are only if the sensor head gets close to the target and integration time lasts long enough. Therefore, working distance and integration time are the dominant factors that affect APXS results. This study confirms the ability of APXS to detect elements and investigates the effects of distance and time on the measurements. We make use of a backup APXS instrument to determine the chemical composition of both powder and bulk samples under the conditions of different working distances and integration times. The results indicate that APXS can detect seven major elements, including Mg, Al, Si, K, Ca, Ti and Fe under the condition that the working distance is less than 30 mm and having an integration time of 30 min. The statistical deviation is smaller than 15%. This demonstrates the instrument's ability to detect major elements in the sample. Our measurements also indicate the increase of integration time could reduce the measurement error of peak area, which is useful for detecting the elements Mg, Al and Si. However, an increase in working distance can result in larger errors in measurement, which significantly affects the detection of the element Mg.